2018
DOI: 10.1051/matecconf/201822401055
|View full text |Cite
|
Sign up to set email alerts
|

Spark plasma and conventional sintering of ZrO2-TiN composites: A comparative study on the microstructure and mechanical properties

Abstract: Spark plasma sintering (SPS) is an extremely fast solidification technique for compounds that are difficult to sinter within the material group metals, ceramics or composites. SPS uses a uniaxial pressure and a very rapid heating cycle to consolidate these materials. This direct way of heating allows the application of very high heating and cooling rates, enhancing densification over grain growth promoting diffusion mechanisms allowing maintaining the intrinsic properties of nanopowders in their fully dense pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…Larger Y-TZP grains are known to exhibit a higher stress-induced tetragonal-to-monoclinic toughening [40]. The same observations relating to MCP-prepared composites were already reported by other authors [34,35,41].…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Larger Y-TZP grains are known to exhibit a higher stress-induced tetragonal-to-monoclinic toughening [40]. The same observations relating to MCP-prepared composites were already reported by other authors [34,35,41].…”
Section: Resultssupporting
confidence: 58%
“…Several recent studies demonstrated an ability to prepare uniformly dense, fine-grained microstructures of either Y-TZP [28,29,30] or TiN [31,32,33] by SPS. However, there are only a handful of studies that have investigated the SPS of Y-TZP-TiN nanocomposites [34,35] that lead to dense composites possessing better mechanical and electrical properties than pure Y-TZP ceramics. The enhanced toughness (7.6 MPa·m 1/2 ) and electrical conductivity (0.12 × 10 −6 S·m −1 ) of composites containing 35 vol% TiN, sintered by FAST (1550 °C for 2 min, applying a pressure of 56 MPa), was reported by Vanmeensel et al [36].…”
Section: Introductionmentioning
confidence: 99%
“…These densification and microstructural behaviour that was achieved was stated to be of good improvement above previous related work by others [94,95]. The Vickers hardness increment was attributed to the effect of TiN content in the composites as it is represented graphically in Figure 7 Pristinskiy et al [99] examined the influence of SPS processing parameters on the densification and mechanical properties of 3% mol-% yttria -ZrO 2 doped with TiN. The ceramic matrix of ZrO 2 was reinforced with 20%, 30%, and 40% TiN, the composites were sintered at 1300-1500°C under 80 MPa for 3 min.…”
Section: The Effects Of Sintering Additives On the Consolidation Of S...supporting
confidence: 63%
“…Pristinskiy et al [99] examined the influence of SPS processing parameters on the densification and mechanical properties of 3% mol-% yttria -ZrO 2 doped with TiN. The ceramic matrix of ZrO 2 was reinforced with 20%, 30%, and 40% TiN, the composites were sintered at 1300–1500°C under 80 MPa for 3 min.…”
Section: The Effects Of Sintering Additives On the Consolidation Of S...mentioning
confidence: 99%
“…This gives the SPS method certain advantages, such as high heating rates (from 100 °C/min to 1000 °C/min) that permit faster densification, which allows sintering at lower temperatures and also with very short cycles, reducing grain growth [ 56 , 57 , 58 , 59 , 60 ]. Moreover, the possibility of applying external pressure during the sintering process makes it possible to carry out the consolidation of poorly sinterable ceramics in very short times, producing materials with better mechanical properties [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%